The effect of KUS121, a novel VCP modulator, against ischemic injury in random pattern flaps. - Koichi Yoshimoto; Ryosuke Ikeguchi; Takashi Noguchi; Maki Ando; Daichi Sakamoto; Terunobu Iwai; Kohei Nishitani; Hanako Ohashi Ikeda; Akira Kakizuka; Shuichi Matsuda (PLoS ONE)
Surgery using skin flaps is essential for soft tissue reconstruction. However, postoperative ischemic injury of the skin flap is a major complication and a top concern after the surgery. Currently, evidence-based drugs to fully prevent ischemic injury are not available. The purpose of this study was to evaluate the effect of KUS121, a VCP modulator, on flap ischemia using a rodent model. 26 Sprague-Dawley rats were randomly divided into two groups. The experimental group was intraperitoneally administered with 100 mg/kg KUS121 dissolved in 5% glucose solution 1 hour before surgery and once per day after surgery. The control group received the same amount of glucose solution on the same schedule. On day 7, 33.6 ± 3.7% of skin flaps in the control group had developed black necrosis compared with 26.4 ± 3.6% in the KUS121 group (p < 0.01). Immunohistochemistry showed that the KUS121 treatment reduced the number of apoptotic cells in the distal third of the flap (p < 0.01); moreover, in the KUS121-treated rats, the number of cells expressing CHOP, an endoplasmic reticulum (ER) stress marker, in the middle third of the flap was significantly lower than in the controls (p < 0.01). We examined the mRNA expression of Ddit3 (CHOP) and Casp3 (caspase-3) on day one after the surgery; mRNA expression of both genes appeared to decrease in the KUS121 group, as compared with the control group, although differences between groups were not significant. Thus, in a random pattern flap, KUS121 reduces ER stress and the number of apoptotic cells, thereby reducing ischemic damage of the flap.